2003
DOI: 10.1002/em.10172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mutagenicity and calf thymus DNA adducts formed by the particulate and semivolatile fractions of vehicle exhausts

Abstract: In this study we compared the ability of extractable organic material from particulate and semivolatile fractions of gasoline emission to induce mutations in bacteria and form adducts with calf thymus (CT) DNA with corresponding data obtained from diesel exhaust. Exhaust particles from gasoline-powered passenger cars were collected on filters and semivolatile compounds were collected on polyurethane foam (PUF). The mutagenicity of the soluble organic fraction (SOF) was determined in Salmonella typhimurium stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Most Ames tests have demonstrated that DEPs and their extracts are mutagenic and closely related to the generation of reactive oxygen species (Pohjola et al, 2003;Tsurudome et al, 1999;DeMarini et al, 2004). However, there is less direct evidence to demonstrate the mutagenicity of DEPs in mammalian cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most Ames tests have demonstrated that DEPs and their extracts are mutagenic and closely related to the generation of reactive oxygen species (Pohjola et al, 2003;Tsurudome et al, 1999;DeMarini et al, 2004). However, there is less direct evidence to demonstrate the mutagenicity of DEPs in mammalian cells.…”
Section: Discussionmentioning
confidence: 98%
“…Genotoxicity is thought to be crucial for the development of malignancy. Numerous in vivo and in vitro studies have suggested that size distribution, surface properties, and adsorbed chemicals are important criteria for the genotoxicity of DEPs (Stoeger et al, 2006;Pohjola et al, 2003). It has been reported that DEP exposure causes DNA and chromosomal damages including bulky DNA adducts, oxidized bases, deletions, and chromosomal aberrations, which may lead to a broad spectrum of mutation (DeMarini et al, 2004;Tsurudome et al, 1999;Muller et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Most Ames tests have demonstrated that DEPs and DPEs are mutagenic and are closely related to the generation of ROS (DeMarini et al 2004; Pohjola et al 2003; Tsurudome et al 1999). At doses greater than 100 μg/mL, Li and colleagues found that the organic extracts of DEPs were able to generate ROS and induce cell death and apoptosis in macrophages (Hiura et al 1999; Li et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies indicate that inhalation of PM results in inflammatory toxicity in the airways and cardiovascular effects (Chen et al 2010; deHaar et al 2006; Maier et al 2008; Oberdorster et al 2000). Although the historical focus of PM toxicity has been on these cardiopulmonary targets, it is now appreciated that inhaled nano-size particulates can quickly exit the lungs and enter the circulation where they distribute (i.e., liver, kidneys, testes, lymph nodes, brain) (Kreyling et al 2004; Oberdorster et al 2002a; Oberdorster et al 2002b) and these organ systems through oxidative stress (Pohjola et al 2003; Samet et al 2004; Schulz 2006). …”
Section: Introductionmentioning
confidence: 99%